Acute effect of pulses based functional muffins on food intake, postprandial glucose and appetite regulation in healthy females - Naseer, Sumayya; Arshad, Muhammad Umair; Imran, Ali; Arshad, Muhammad Sajid; Saeed, Farhan; Ahmad, Aftab; Imran, Muhammad; Naeem, Usman (Progress in Nutrition, 2019)
Background/Aims: The core intention of recent exploration was to investigate the impact of pulse based dietary intervention (muffins) on blood Glucose (BG) & average appetite before and after an ad libitum pizza meal and on food intake (FI).  Methods: Purposely, a crossover, repeated measure design was adapted by involving 12 healthy females (18–30 years old: with a normal BMI 20–24·9 kg/m2) randomly provided 4 treatments (isovolumetric and isocaloric): T1 (control: muffin without pulses), T2 (Lentil based muffins prepared by pulses floor replacement @ 20% with conventional floor), T3 (Mung bean based muffins prepared by pulses flour replacement @ 20% with conventional floor) and T4 (Combination of Lentil+Mung bean based muffins prepared by pulses floor replacement @ 10+10%, respectively with conventional floor), followed by a provision of pizza meal after the 120minutes. BG and average appetite was measured at 0, 15, 30, 45, 60, 90 and 120 minutes for pre meal and 140 and 170 minutes for post meal. Whereas, food intake was measured at a pizza meal (140 minutes). Results: The pulses based muffins caused reduced food intake (pT1>T0. Conclusion: Conclusively, the type of pulses has stronger influence on short term glucose, average appetite and reduce food intake after subsequent meal might be due to difference in their protein contents. The pulses with higher protein exhibited better glycemic control. Moreover, pulses based functional foods should be developed to tackle the glycemic responses owing to their appetite and food intake lowering perspective.